From Trash to Treasure: Assessing the Effectiveness of the Green@Community Recycling Network in Hong Kong - Teressa H. C. Chan; Tin Yan Hui; Janet K. Y. Chan (Recycling)
Municipal solid waste (MSW) is a growing problem worldwide posing a variety of environmental and human health impacts. Despite recycling being one major strategy to alleviate MSW production, the effectiveness of recycling has been equivocally dependent on local policy implementation and citizen environmental behavior. To enhance recycling effectiveness in Hong Kong, the government has established Green@Community, a unified community-based network for recycling and public environmental education. Since its establishment, the number of visitors to and the amount of recyclable materials collected at the network increased steadily over time. Our study is the very first to investigate the effectiveness of this territory-wide recycling network. Through a questionnaire survey, we found that respondents’ recycling traits were stronger if they have accrued gift tokens through participating in recycling activities. Visiting a Green@Community facility could also enhance knowledge of the types of acceptable recyclables, and respondents who had visited a Green@Community facility agreed that education and publicity could increase the recycling rate in Hong Kong. These findings highlighted the effectiveness and uniqueness of this community-based recycling network, its role in raising recycling knowledge, and its implications for policymakers and urban planners of densely populated cities to leverage society’s recycling participation, but also called for more efforts on developing, promoting, and incentivizing the usage of such a network to further enhance recycling and alleviate MSW production in Hong Kong.